PENGARUH EDUKASI KEPADA KADER POSYANDU MENGGUNAKAN BOOKLET TERHADAP PENINGKATAN PENGETAHUAN TENTANG METODE KONTRASEPSI JANGKA PANJANG (MKJP) - Widya Nengsih; Sinta Ulandari (Universitas Fort de Kock Bukittinggi, 2022)
The use of MKJP (Long-Term Contraceptive Method) is still very low at 17.45%. Meanwhile, 81.23% are non-MKJP family planning users and 1.32% are using traditional family planning methods. One of the causes of the low use of MKJP is the low knowledge of cadres so that cadres are not able to provide MKJP family planning counseling to WUS properly and provide motivation to increase interest in longterm contraceptive user. This research is a pre-experimental research that is one group pretest-posttest to see the effect of education to posyandu cadres using booklets on increasing knowledge about Long Term Contraception Methods (MKJP). The population in this study were all cadres in the working area of Sungai Baung Health Center as many as 65 cadres. The number of samples in this study were 44 cadres using the quata sampling technique. The research was conducted in August 2022 in the working area of Sungai Baung Health Center. The instrument used in this research is Booklet. The statistical test used to analyze the data for the two variables was using a T-test with a significance level of 5%. The results showed that the average knowledge of MKJP before education was 12.63 and after it was carried out it increased to 17.47 with an average increase of 4.833. Based on statistical tests, it is known that the p-value is 0.000, which means that there is an effect of education for posyandu cadres using booklets on increasing knowledge about Long-Term Contraception Methods (MKJP) in the Sungai Baung Health Center Work Area, Sarolangun Regency in 2022. It is hoped that the booklet media used in this study can be used as an educational medium in providing or conducting training to cadres about MKJP. Keywords: Knowledge, Booklet and MKJP